Building STEM inquiry-based teaching proposal through collaborations between schools and research centres: students' and teachers' perceptions. - Lupión-Cobos, Teresa; Girón-Gambero, Jesús Ramón; García-Ruiz, Cristina (Eurasian Society of Educational Research, 2022)
This study presents an inquiry-based teaching approach using a rich methodology involving STEM (science-technology- engineering and mathematics) projects, developed using a cooperative way to work between schools and research centres. We describe the teaching pattern scenario with students, teachers, and scientists. We also illustrate the learning process, conducted through two inquiry-based problems in Biochemistry, the mutagenesis process and the transgenesis effects caused by inoculation of bacteria. The teaching sequence, as well as the scientific knowledge and students’ competencies involved, are shown. We then analyse the students' and teachers' perceptions in this scenario regarding the development of students' STEM learning through their inquiry skills promoted and concerning predictors to vocational careers involved (students’ identities as potential scientists, scientific attitudes, social implications towards science or students´ agency). Finally, we add some conclusions and contributions to teaching STEM education, related to factors of the design teaching scenario that bring connections with the interests and motivations of students, such as the relevance of the projects to evoke understanding of processes or causal relationships of content or the teacher's professionalisation supported by a proper allocation between scientists and teachers.
This work was part of the FECYT project FCT-12-3552 “Introduction to Innovation and Investigation in Secondary Education in Andalusia” funded by the Spanish Ministry of Economy, the R&D project PID2019-105765GA-I00 “Citizens with critical thinking: a challenge for teachers in science education”, funded by the Spanish National R&D Plan, and the Coordination Project “Development of Teaching Competencies in PST of Early Childhood, Primary and Secondary Education, with the teaching of scientific practices of inquiry and STEM approaches in science education. Coordination for the improvement of educational practice, funded by the University of Málaga. The authors wish to acknowledge all participants in the project.
Keywords: Genética - Estudio y enseñanza; Ciencia - Estudio y enseñanza; Investigación activa en educación; STEM education; Genetic problems; Inquiry-based learning; Students-teachers-scientists collaboration